Quality of Dental Services in People with no Social Security - Hernández-Morales, Magdoly; Mota-Morales, María de Lourdes; Ortiz-Chacha, Christian S; Rodríguez-Romero, Edit; Gutiérrez-Alba, Gaudencio (Horizonte Sanitario, 2022)
Objective: Assess the quality of dental care among population with no social security treated in primary care units.Material and methods: An observational, descriptive, exploratory, and cross-sectional study was conducted to assess, through structure, process and results. Also, 86 clinical records, seven (7) medical offices, 168 users and 43 dentists were reviewed. Three checklists and a questionnaire were the tools used.Results: The total quality index was that of 69.73, while for structure, process and the result was 72.9%, 54.61 and 81.6 respectively. There is a lack of supplies, instruments, dental units and surplus of dentists, as well as technical and regulatory non-compliance.Conclusions: Comprehensive evaluation of quality of dental care through measuring the structure, processes, and results, enables to identify areas of opportunity and scientific evidence-based decision making.Keywords: Quality of health care; Public health dentistry; Practice guidelines; Medical records; Healthcare